Activating transcription factor 3 (ATF3) protects against lipopolysaccharide‐induced acute lung injury via inhibiting the expression of TL1A. Issue 12 (15th May 2017) - Qian, Lanlan; Zhao, Yunfeng; Guo, Liang; Li, Shaoying; Wu, Xueling
Abstract : Excessive inflammatory responses are critical in the pathogenesis of acute lung injury (ALI). Activating transcription factor 3 (ATF3) is a stress‐induced transcriptional regulator that is a negative regulator of inflammatory responses. Therefore, we investigated the role and signaling pathways of ATF3 in lipopolysaccharide (LPS)‐induced ALI in mice. The mouse macrophage RAW264.7 cells were cultured on HTS 24‐Transwell filter plates in presence of ATF3 siRNA before exposure to LPS. ATF3 knock‐out (KO) and wild type (WT) mice were challenged by intra‐peritoneal injection of LPS (15 mg/kg). Gene analysis was used to analyze differential gene expression between ATF3 KO and WT mice. LPS increased the expression of ATF3 in RAW264.7 cells and in lung tissues of mice, The concentration of TNFα and IL‐6 was significantly increased in ATF3 siRNA‐treated RAW264.7 cells compared to control cells after LPS stimulation. The concentration of TNFα, IL‐6 and IL‐1β in serum and lung tissue of ATF3 KO mice was significantly increased compared to ATF3 WT mice. In addition, the lung wet/dry weight and BALF protein were significantly increased in ATF3 KO mice after LPS injection at 6, 24, and 48 hr. The survival of ATF3 KO mice significantly decreased. Differential gene analysis showed that TL1A was highly expressed in LPS‐induced lung tissues of ATF3 KO mice.Moreover, ATF3 down‐regulated the expression of TL1A in RAW264.7 cells and in lung tissues. These findings suggest that ATF3 protects against LPS‐induced ALI via inhibiting TL1A expression. Abstract : Excessive inflammatory responses are critical in the pathogenesis of acute lung injury (ALI). Activating transcription factor 3 (ATF3) is a stress‐induced transcriptional regulator that is a negative regulator of inflammatory responses.The survival of ATF3 KO mice significantly decreased. Differential gene analysis showed that TL1A was highly expressed in LPS‐induced lung tissues of ATF3 KO mice.Moreover, ATF3 down‐regulated the expression of TL1A in RAW264.7 cells and in lung tissues.These findings suggest that ATF3 protects against LPS‐induced ALI via inhibiting TL1A expression.